Respon of Jabon Seedling Growth (Anthocephalus cadamba Roxb.) on Giving Compost and Cococnet Shell Charcoal in Mine Waste Sand Media - Basuki Wasis; Desi Ratnasari (Jurnal Silvikultur Tropika, 2013)
Sand mining activities potentially disturb the ecosystem of the river. The residu of the activity causing the contaminated water by sand. Utilization of waste sand into a mine planting media jabon. (Roxb Anthocephalus cadamba Miq.) need to be tested. Jabon is one of various species of industrial raw material wood. This research aims to analyze the response jabon growth for giving compost and charcoal coconut shell on the sand mining waste media. The research design used is factorial experiment with complete random design. The results showed that the interaction between composting and coconut shell charcoal give real effect on height and total dry weight parameter. The addition of compost 60 grams and coconut shell charcoal 3% into the mine waste sand media can increase the total dry weight of jabon.